Current status of safety engineering education in China. Issue 2 (13th September 2021) - Ma, Congming; Jing, Mingjv; Hou, Shuya; Jiang, Juncheng; Zhang, Bin
Abstract: An overview of Safety Engineering education in China is conducted. First, definition, research specialty, and development history of Safety Science and Engineering are introduced. Second, a geographical distribution study indicates that universities offering Safety Engineering in mainland China are mainly located in East China, Central North China, and some provinces in West and South China, which is consistent with the latest gross domestic product (GDP) and year‐end resident population data. The analysis of evaluation in higher education focuses on engineering education accreditation, first‐class discipline construction, and China University Subject Rankings. Third, Safety Engineering curricula in China mainly include general education courses and professional courses. The former is divided into basic education courses and subject education courses, and the latter is divided into professional core courses and professional characteristic courses. The professional characteristic courses offered by various universities are different from each other, mainly due to their research specialties, such as fire safety, chemical safety, mining safety, construction safety, and nuclear safety. Finally, existing challenges, including a lack of engineering practice, lack of systematic course content, and lack of professional competitiveness, are discussed.